2010
DOI: 10.3109/02699051003652831
|View full text |Cite
|
Sign up to set email alerts
|

The Morfeo Study: A 1-year follow-up of complications of vegetative state in a dedicated facility

Abstract: The data that proved significant suggest a minimum set of quality-of-care indicators in VS patients: pressure sores follow-up, nutritional status, ROM and incidence of infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…After screening for titles and abstracts, 219 full‐length articles were selected, of which 30 met the inclusion criteria. Three [13–15] out of these 30 studies were excluded from the quantitative analyses because the outcome of the anoxic patients could not be retrieved. Twenty‐three out of the 27 included studies reported all outcomes of interest.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After screening for titles and abstracts, 219 full‐length articles were selected, of which 30 met the inclusion criteria. Three [13–15] out of these 30 studies were excluded from the quantitative analyses because the outcome of the anoxic patients could not be retrieved. Twenty‐three out of the 27 included studies reported all outcomes of interest.…”
Section: Resultsmentioning
confidence: 99%
“…The selected studies included an overall sample of 2844 patients with disorders of consciousness (eight in coma, 0.3%; 1774 in VS/UWS, 62.4%; 926 in MCS, 32.6%; 136 having emerged from MCS [eMCS], 4.7%) caused by different aetiologies (traumatic brain injury 992, 34.9%; non‐traumatic brain injury 1852, 65.1%), with a mean age of 48 years (not available in two studies); 1825 (64.2%) patients were male (not available in one study). Most studies [3, 5, 13–19, 21, 23, 24, 26, 31, 32, 35, 36, 39, 40] investigated the prognostic role of demographic, clinical and anamnestic factors. Some studies also included neurophysiological [5, 16, 19, 20, 22, 23, 25, 28, 30, 32, 33, 38] or neuroimaging [15, 26, 29, 37–39] investigations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…prevention of pressure sores, contractures, pneumonia). In the past decade, some practitioners and researchers have shifted from the term “treatment” towards “quality management” (von Wild et al , 2007), and literature addressing these issues from PT's perspectives tend to agree (Farmer and James, 2001; Reddy et al , 2006; Fabbri et al , 2010). Still, the question of rehabilitation, improvement of technology, and creating means to better understand consciousness, are still debated intensively (Lotze et al , 2011; Monti et al , 2010; Owen et al , 2006; Owen and Coleman, 2008).…”
Section: Introductionmentioning
confidence: 99%